Microglia as a Hub for Suicide Neuropathology: Future Investigation and Prevention Targets - Gonçalves de Andrade, Elisa; González Ibáñez, Fernando; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2022)
Suicide is a complex public health challenge associated worldwide with one death every 40 s. Research advances in the neuropathology of suicidal behaviors (SB) have defined discrete brain changes which may hold the key to suicide prevention. Physiological differences in microglia, the resident immune cells of the brain, are present in post-mortem tissue samples of individuals who died by suicide. Furthermore, microglia are mechanistically implicated in the outcomes of important risk factors for SB, including early-life adversity, stressful life events, and psychiatric disorders. SB risk factors result in inflammatory and oxidative stress activities which could converge to microglial synaptic remodeling affecting susceptibility or resistance to SB. To push further this perspective, in this Review we summarize current areas of opportunity that could untangle the functional participation of microglia in the context of suicide. Our discussion centers around microglial state diversity in respect to morphology, gene and protein expression, as well as function, depending on various factors, namely brain region, age, and sex.